Non‐internalizing antibody–drug conjugates display potent anti‐cancer activity upon proteolytic release of monomethyl auristatin E in the subendothelial extracellular matrix. Issue 7 (30th December 2016) - Gébleux, Rémy; Stringhini, Marco; Casanova, Ruben; Soltermann, Alex; Neri, Dario
Abstract : Antibody–drug conjugates (ADCs) represent a promising class of biopharmaceuticals with the potential to localize at the tumor site and improve the therapeutic index of cytotoxic drugs. While it is generally believed that ADCs need to be internalized into tumor cells in order to display optimal therapeutic activity, it has recently been shown that non‐internalizing antibodies can efficiently liberate disulfide‐linked drugs at the extracellular tumor site, leading to potent anti‐cancer activity in preclinical animal models. Here, we show that engineered variants of the F16 antibody, specific to a splice isoform of tenascin‐C, selectively localize to the subendothelial tumor extracellular matrix in three mouse models of human cancer (U87, A431, MDA‐MB‐231). A site‐specific coupling of F16 in IgG format with a monomethyl auristatin E (MMAE) derivative, featuring a valine‐citrulline dipeptide linker equipped with a self‐immolative spacer, yielded an ADC product, which cured tumor‐bearing mice at a dose of 7 mg/Kg. The observation of an efficient extracellular proteolytic cleavage of the valine‐citrulline linker was surprising, as it has generally been assumed that this peptidic structure would be selectively cleaved by cathepsin B in intracellular compartments. The products described in this article may be useful for the treatment of human malignancies, as their cognate antigen is strongly expressed in the majority of human solid tumors, lymphomas and aggressive leukemias, while being virtually undetectable in most normal adult tissues. Abstract : What's new? Antibody– drug conjugates consist of a tumor‐seeking antibody, a payload (cytotoxic agent), and a linker connecting the two. Following internalization by targeted cancer cells, the components separate, with cell uptake considered essential for optimal therapeutic activity. This study shows, however, that non‐internalizing antibody–drug conjugates, equipped with peptide‐based linker‐payload combinations, can efficiently release cytotoxic drugs in the tumor stroma, with potent therapeutic activity in mouse models of human cancer. The study may be of clinical relevance, as it used a clinical‐stage antibody (F16) and the linker‐payload combination of an approved biopharmaceutical (brentuximab vedotin).